Perceptions of complementary, alternative, and integrative medicine: A global cross-sectional survey of cardiology researchers and clinicians - Jeremy Y. Ng; Mehvish Masood; Sivany Kathir; Holger Cramer (PLoS ONE, 2025)
Background Complementary, alternative, and integrative medicine (CAIM) has been increasing in popularity among patients with cardiovascular illnesses. However, little is known about perceptions of CAIM among cardiology researchers and clinicians. In response, this study aimed to assess the practices, perceptions, and attitudes towards CAIM among cardiology researchers and clinicians. Methods An anonymous, digital cross-sectional survey was administered to researchers and clinicians who have published articles in cardiology journals indexed in OVID MEDLINE. The survey was sent to 37,915 researchers and clinicians and included 5-point Likert scales, multiple-choice questions, and open-ended questions. Basic descriptive statistics were drawn from quantitative data, and a thematic content analysis was conducted to analyze open-ended responses. Results Among the 309 respondents, the majority (n = 173, 55.99%) identified themselves as both researchers and clinicians in the field of cardiology. While 45.78% (n = 114) of participants expressed agreement regarding the safety of CAIM therapies, 44.40% (n = 111) disagreed on their efficacy. Most respondents believed in the value of conducting research on CAIM therapies (79.2%, n = 198). Respondents perceived mind-body therapies (57.61%, n = 159) and biologically based practices (47.46%, n = 131) as the most promising interventions for the prevention and treatment of cardiovascular conditions. Biofield therapies were the least favoured for integration into mainstream medical practices (11.93%, n = 29). Conclusions While cardiology researchers and clinicians perceive CAIM therapies to have potential, many are hesitant about integrating such interventions into the current medical system due to a perceived lack of scientific evidence and standardized products. Insights from this study may help establish educational resources for healthcare practitioners.